DEVELOPMENT OF LKPD BASED ON BRAIN BASED LEARNING USING CROSSWORD PUZZLES ON THE TOPIC OF ARITHMETIC SERIES AND SEQUENCES FOR CLASS X MAS DARUL ISTIQOMAH PADANGSIDIMPUAN - Febri Yanti Tanjung; A. Naashir M. Tuah Lubis; Sakinah Siregar (PT. Jurnal Center Indonesia Publisher, 2025)
This study is motivated by the lack of use of mathematics learning tools such as student worksheets (LKPD) at MAS Darul Istiqomah Padangsidimpuan, where teacher handbooks and textbooks are more frequently used. Additionally, the students' mathematics learning outcomes, particularly in the topic of arithmetic sequences and series, are low. This study aims to assess the validity, practicality, and effectiveness of student worksheets (LKPD) based on brain-based learning (BBL) using crossword puzzles in the topic of arithmetic sequences and series for class X at MAS Darul Istiqomah Padangsidimpuan. This research is a research and development (R&D) study. The development model used in this research is the 4D model, which consists of four stages: Define, Design, Development, and Disseminate. The validation of the LKPD includes material validation, media validation, and language validation. The trial was conducted in class X-B, with a total of 19 students at MAS Darul Istiqomah Padangsidimpuan. The material experts, media experts, and language experts each consisted of 2 validators. The results of this study indicate that the developed LKPD meets the eligibility criteria, with an overall validation percentage of 87.32%, categorized as valid. The practicality of all aspects is shown by a value of 85.63%, categorized as very practical. The effectiveness is indicated by an average student learning outcome score of 71%, calculated from the overall average learning outcomes of the students, categorized as effective. Therefore, it can be concluded that the LKPD is feasible, engaging, and capable of improving student learning outcomes.